Advertisement for a painting of two 'grandi sacrificati'. From: Il Martello, NY, 11-07-1931 (ZF 6121) - Tamburrino, Toto',
Advertisement for a painting of two 'grandi sacrificati'. From: Il Martello, NY, 11-07-1931 (ZF 6121).